2020
DOI: 10.1093/mnras/staa1056
|View full text |Cite
|
Sign up to set email alerts
|

Not all stars form in clusters – Gaia-DR2 uncovers the origin of OB associations

Abstract: Historically, it has often been asserted that most stars form in compact clusters. In this scenario, present-day gravitationally-unbound OB associations are the result of the expansion of initially gravitationally-bound star clusters. However, this paradigm is inconsistent with recent results, both theoretical and observational, that instead favour a hierarchical picture of star formation in which stars are formed across a continuous distribution of gas densities and most OB associations never were bound clust… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 60 publications
5
64
0
Order By: Relevance
“…Clustering of young massive stars in star-forming regions has a profound effect on the structure and evolution of the ISM on 100 pc scales with a possibility of the break out of the thin HI Galactic disc in the form of chimneys (Mac Low and McCray, 1988;Tomisaka and Ikeuchi, 1986;Kim et al, 2017;El-Badry et al, 2019). The massive star-forming regions are structured as they are observationally represented by compact clusters of young massive stars as well as by highly substructured OB associations with lower stellar density than in the compact clusters (see, e.g., Krumholz et al, 2019;Ward et al, 2019). The winds of massive stars and their subsequent SNe create large-scale superbubbles and supershells in the ISM through their great momentum and energy release (see, e.g., Heiles, 1979;Mac Low and McCray, 1988;El-Badry et al, 2019).…”
Section: Low-energy Cosmic Rays In Superbubblesmentioning
confidence: 99%
“…Clustering of young massive stars in star-forming regions has a profound effect on the structure and evolution of the ISM on 100 pc scales with a possibility of the break out of the thin HI Galactic disc in the form of chimneys (Mac Low and McCray, 1988;Tomisaka and Ikeuchi, 1986;Kim et al, 2017;El-Badry et al, 2019). The massive star-forming regions are structured as they are observationally represented by compact clusters of young massive stars as well as by highly substructured OB associations with lower stellar density than in the compact clusters (see, e.g., Krumholz et al, 2019;Ward et al, 2019). The winds of massive stars and their subsequent SNe create large-scale superbubbles and supershells in the ISM through their great momentum and energy release (see, e.g., Heiles, 1979;Mac Low and McCray, 1988;El-Badry et al, 2019).…”
Section: Low-energy Cosmic Rays In Superbubblesmentioning
confidence: 99%
“…Over the past decade, this view has been challenged on multiple occasions (e.g., Elmegreen 2008;Bressert et al 2010;Kruijssen 2012;cf. Parker & Meyer 2012), where the Gaia mission (Gaia Collaboration et al 2016) and particularly the second data release (Gaia DR2;Gaia Collaboration et al 2018) have recently initiated a renaissance in our understanding of the predominant conditions for star formation (e.g., Wright & Mamajek 2018;Cantat-Gaudin et al 2019a;Kuhn et al 2019;Wright et al 2019;Ward et al 2020). These insights have been promoted mostly by investigating the large-scale structure and kinematics of massive OB associations with ages up to a few million years.…”
Section: Introductionmentioning
confidence: 99%
“…In this picture supersonic turbulence introduces fluctuations in the density distribution of the giant molecular cloud, with localized high-density regions producing bound clusters, while low-density regions drive the formation of dispersed unbound stellar populations. In this way, most OB associations were never bound clusters, but instead, they were formed in situ in low-density environments following the fractal and velocity structure of the gas from which they form (e.g., Ward et al 2020;Gouliermis 2018), as was already observed by Wright et al (2014), who find for Cyg OB2 that massive stars can form in relatively low-density environments. In this frame, because OB stars in NGC 6357 are clustered while they distribute more as an association in NGC 6334, we can speculate that NGC 6357 OB stars originate from denser conditions than the ones in NGC 6334.…”
Section: Discussionmentioning
confidence: 79%